Ayurvedic Management in Chronic Refractory Mukhadushika (∼Acne Vulgaris): A Case Report - Priyanka Thakur; Varisha Rehman; Sandeep Singh Tiwari; Rupashri Nath (Indian Journal of Health Sciences and Biomedical Research KLEU, 2026)
Chronic refractory Mukhdushika, closely correlated to Acne Vulgaris, represents significant therapeutic hurdles due to its relapsing nature and partial responsiveness to treatment. This case report describes a 26-year-old male with a total of 8 years of recurrent papulopustular acne associated with pain, burning sensation, itching, and post inflammatory hyperpigmentation. According to the Ayurvedic assessment, Pitta pradhan tridoshaja involvement with agnidushti and ama leaded to strotorodha. Dosha pratyanika chikitsa was planned, including agnideepana, ama pachana, rakta prasadana, nitya virechana, followed by strict nidana parivarjana, yoga, and lifestyle modification. Relapsing tendency and inflammatory lesions gradually decreased, indicating the efficacy of this individualized Ayurvedic approach in achieving sustainable clinical healing.